2011
DOI: 10.5194/acp-11-11041-2011
|View full text |Cite
|
Sign up to set email alerts
|

Illustrating the benefit of using hourly monitoring data on secondary inorganic aerosol and its precursors for model evaluation

Abstract: Abstract. Secondary inorganic aerosol, most notably ammonium nitrate and ammonium sulphate, is an important contributor to ambient particulate mass and provides a means for long range transport of acidifying components. The modelling of the formation and fate of these components is challenging. Especially, the formation of the semi-volatile ammonium nitrate is strongly dependent on ambient conditions and the precursor concentrations. For the first time an hourly artefact free data set from the MARGA instrument… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 43 publications
5
54
0
Order By: Relevance
“…As listed in Table 1, the concentration of NH 3 at the NCP rural site was lower than that reported at Asian and African urban sites such as Lahore (Pakistan; Biswas et al, 2008), Colonelganj (India; Behera and Sharma, 2010), and Cairo (Egypt; Hassan et al, 2013) but higher than those from other areas in China, Europe, and North America (Plessow et al, 2005;Yao et al, 2006;Lin et al, 2006;Walker et al, 2006;Hu et al, 2008;Meng et al, 2011Meng et al, , 2014Shen et al, 2011;Schaap et al, 2011;Makkonen et al, 2012;Behera et al, 2013;Gong et al, 2013;Li et al, 2014). For example, the NH 3 at the NCP rural site was higher than that found at the Shangdianzi regional background station in the NCP (Meng et al, 2011), Lin'an regional background station in the Yangtze River Delta (YRD) in eastern China (Meng et al, 2014), and the rural site in Beijing .…”
Section: Overview Of Concentration Levels Of Measured Speciesmentioning
confidence: 91%
“…As listed in Table 1, the concentration of NH 3 at the NCP rural site was lower than that reported at Asian and African urban sites such as Lahore (Pakistan; Biswas et al, 2008), Colonelganj (India; Behera and Sharma, 2010), and Cairo (Egypt; Hassan et al, 2013) but higher than those from other areas in China, Europe, and North America (Plessow et al, 2005;Yao et al, 2006;Lin et al, 2006;Walker et al, 2006;Hu et al, 2008;Meng et al, 2011Meng et al, , 2014Shen et al, 2011;Schaap et al, 2011;Makkonen et al, 2012;Behera et al, 2013;Gong et al, 2013;Li et al, 2014). For example, the NH 3 at the NCP rural site was higher than that found at the Shangdianzi regional background station in the NCP (Meng et al, 2011), Lin'an regional background station in the Yangtze River Delta (YRD) in eastern China (Meng et al, 2014), and the rural site in Beijing .…”
Section: Overview Of Concentration Levels Of Measured Speciesmentioning
confidence: 91%
“…Yet another method that is based on the same principle is the Dionex Gas Particle Ion Chromatography (GPIC) system that measures concentrations of water-soluble inorganic aerosol constituents (Cl − , NO ) and their associated precursor gases (HCl, SO 2 , HNO 3 , NH 3 ) (Godri et al, 2009). The ability to measure both water-soluble aerosol and the precursor gas concentrations at a high time resolution has recently been shown to be especially valuable for evaluating models, for instance the secondary inorganic aerosol formation (Schaap et al, 2011) and the gas-aerosol partitioning of ammonium nitrate (Aan de Brugh et al, 2012).…”
Section: U Makkonen Et Al: Semi-continuous Gas and Inorganic Aerosomentioning
confidence: 99%
“…Through statistical analysis for both measured and modeled data points, Gilardoni et al [2011] pointed out that monthly or annual mean observations might not be suitable for evaluating BC modeling. Schaap et al [2011] illustrated that using observational data with higher temporal resolution (hourly data) generated more accurate model evaluation for secondary inorganic aerosols. Only two studies were found to use the hourly data [Hakami et al, 2005;Kondo et al, 2011b].…”
Section: Introductionmentioning
confidence: 99%